2009
DOI: 10.1051/0004-6361/200911746
|View full text |Cite
|
Sign up to set email alerts
|

Multi-frequency imaging of the galaxy cluster Abell 2163 using the Sunyaev-Zel'dovich effect

Abstract: Context. Observations of the Sunyaev-Zel'dovich effect (SZE) from galaxy clusters are emerging as a powerful tool in cosmology. Besides large cluster surveys, resolved SZE images of individual clusters can shed light on the physics of the intra-cluster medium (ICM) and allow accurate measurements of the cluster gas and total masses. Aims. We used the APEX-SZ and LABOCA bolometer cameras on the APEX telescope to map both the decrement of the SZE at 150 GHz and the increment at 345 GHz toward the rich and X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 63 publications
4
42
0
Order By: Relevance
“…First detected by Wilbanks et al (1994) and used to determine the Hubble constant in Holzapfel et al (1997), A2163 is the first galaxy cluster detected in the submm band (Lamarre et al 1998). A recent analysis of its SZ signal by Nord et al (2009) has confirmed the exceptionally high temperature of its hot gas content independently of X-ray analyses.…”
Section: Introductionmentioning
confidence: 99%
“…First detected by Wilbanks et al (1994) and used to determine the Hubble constant in Holzapfel et al (1997), A2163 is the first galaxy cluster detected in the submm band (Lamarre et al 1998). A recent analysis of its SZ signal by Nord et al (2009) has confirmed the exceptionally high temperature of its hot gas content independently of X-ray analyses.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, observations of the Sunyaev-Zeldovich effect (SZE) from galaxy clusters are becoming a powerful tool Article published by EDP Sciences L14, page 1 of 4 in cosmology (Sunyaev & Zeldovich 1972;Cavaliere & FuscoFermiano 1978;De Filippis et al 2005;Cunha et al 2007b;Nord et al 2009;Basu et al 2010). The combination of SZE and X-ray provides the D A (z) of galaxy clusters, hence can be used to constrain some cosmological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Dedicated instruments now produce high resolution images of single objects (e.g. Kitayama et al 2004;Halverson et al 2009;Nord et al 2009) and moderately large samples of high-quality SZ measurements of previously-known clusters (e.g., Mroczkowski et al 2009;Plagge et al 2010). In addition, large-scale surveys for clusters using the SZ effect are underway, both from space with the Planck mission (Valenziano et al 2007;Lamarre et al 2003) and from the ground with several dedicated telescopes, such as the South Pole Telescope ) leading to the first discoveries of clusters solely through their SZ signal (Staniszewski et al 2009).…”
Section: Introductionmentioning
confidence: 99%